Colônias de povoamento versus colônias de exploraç\~ao: De heeren a acemoglu - Leonardo Monteiro Monasterio; Philipp Ehrl (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The paper examines the evolution of the thesis which states that the type of colonization determines, or conditions, the future of societies. Adam Smith already presented this proposition and a typology of colonies. However, it were the German authors Heeren and Roscher, in the 19th century, who developed the thesis. These historians influenced the French orthodox economist Leroy-Beaulieu, who dealt with the issue in a work published in 1902. Clearly, Caio Prado Jr. was another promoter of the dichotomy "settlement colony versus extractive/exploitation colony" in Brazil rather than its creator. In the United States, the idea resurfaces in the works of Douglass North (1955 and 1959) and Richard Baldwin (1957). More recently, cliometricians as Engerman and Sokoloff (1997) developed the proposition without reference to the European authors. Finally, Acemoglu, Johnson and Robinson (2001 and 2002) introduced the thesis to a wider academic audience and offered econometric evidence. The present paper concludes with a discussion on the possible reasons for the success of the thesis and its recurring "discovery" by researchers.
Keywords: B00; N01; 330; immigration; settlements; extractive colonies